Association between Paraoxonase -1 Gene Pro-moter T (-107) C Polymorphism and Coronary Artery Disease - M Najafi; L Hosseini Gohari; M Firoozrai; A Zavarehee; HA Basiri (Tehran University of Medical Sciences, 2008)
Background: Paraoxonase-1(PON1), a high-density lipoprotein (HDL) associated enzyme, is believed to contribute in the pathogenesis of coronary artery disease (CAD). The aim of this study was to evaluate the association of PON1 promoter C (-107)T polymorphism with the extent of coronary artery stenosis in Iranian patients. Methods: The RFLP analysis for determination of the C(-107)T genotype distribution and measurement of serum PON1 activities (Paraoxonase and Arylesterase) were performed in 99 patients. They were undergone coronary angiography to determine the number of stenotic vessels and classified into three groups: single vessel disease (SVD), two vessels disease (2VD) and three vessels disease (3VD). Results: The C(-107)T polymorphism was significantly associated with serum arylesterase activity but not with paraoxonase activity. The CC and TT genotypes distributed inversely in SVD as compared with 3VD group. Moreover, the CC high activity genotype frequency decreased with increase of stenotic vessels in patients. Conclusion: The reduced arylesterase activity as a function from the weak promoter activity increases the stenosis severity, so that, we assume it is one of the progressive factors of atherosclerotic process in stenotic vessels.